Sensitivity and specificity of the Alvarado Score in the diagnosis of patients treated for acute appendicitis in hospitals of Cusco - Meléndez Flores, Jhuvitza Estela (2019)
Objective: To determine the sensitivity and specificity of the Alvarado Score for the diagnosis of patients with acute appendicitis treated in hospitals of Cusco during the period from 2011 to 2016. Materials and methods: A descriptive, cross-sectional and observational study. The medical records of 316 patients treated for acute appendicitis during the period from 2011 to 2016 in the Surgery Department of three hospitals in the city of Cusco were reviewed. With a non-probabilistic convenience sampling, the Alvarado Score variable was defined by clinical assessment, and the histopathological analysis was the diagnostic gold standard. The SPSS Statistics 22.0 was used, and the variable was analyzed with sensitivity and specificity tests. Positive and negative predictive values were established, and the receiver operating characteristic (ROC) curve analysis was used. Results: The average age was 34 years, 55.7 % were male, and the average disease duration was 16 hours. Out of the total evaluation, 13.6 % of the patients had a histopathological diagnosis ruling out acute appendicitis, from which 11.9 % were males and 15.7 % were females. The Alvarado Score presented a sensitivity of 78 %, specificity of 44.2 %, positive predictive value of 89.8 %, and negative predictive value of 13.3 %. The area under the ROC curve was 61.1 %. Conclusions: The Alvarado Score had a high percentage of sensitivity and a good specificity regarding the histopathological diagnosis.